FUNCTIONAL BRAIN ASYMMETRY AS A FACTOR OF THE REPRODUCTION AND PERCEPTION OF METAPHORS - Zubyashvili, Iryna; Melnychuk, Tetiana; Lytvynenko, Olga; Ulianova, Tetiana; Shetelia, Natalia (International Journal of Psychosocial Rehabilitation, 2020)
The article considers the scientific aspects of metaphors; understanding of a metaphor in psychology is highlighted; peculiarities and properties of a metaphor as a method used at psychological work are analyzed. It shows that heuristic metaphors are important for explaining the complex processes of human consciousness. The studies revealing the relations of cerebral hemisphere asymmetry with a person’s adaptation and behaviour, verbal and non-verbal intelligence, information perception and processing, stability of homeostasis, emotional, hormonal, autonomic and also immune reactions are analysed. Brain asymmetry is regarded as one of the fundamental objective laws of cerebral hemisphere organization that is manifested not only in morphology but also in asymmetry of mental processes and influences the reproduction and perception of metaphors.